The Case for a Normatively Charged Approach to Regulating Shadow Banking - Multipolar Regulatory Dialogues as a Means to Detect Tail Risks and Preclude Regulatory Arbitrage - Matthias Thiemann; Tobias Trog̈er (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2020)
This paper contributes to the debate on the adequate regulatory treatment of non-bank financial intermediation (NBFI). It proposes an avenue for regulators to keep regulatory arbitrage under control and preserve sufficient space for efficient financial innovation at the same time. We argue for a normative approach to supervision that can overcome the proverbial race between hare and hedgehog in financial regulation and demonstrate how such an approach can be implemented in practice. We first show that regulators should primarily analyse the allocation of tail risk inherent in NBFI. Our paper proposes to apply regulatory burdens equivalent to prudential banking regulation if the respective transactional structures become only viable through indirect or direct access to (ad hoc) public backstops. Second, we use insights from the scholarship on regulatory networks as communities of interpretation to demonstrate how regulators can retrieve the information on transactional innovations and their risk-allocating characteristics that they need to make the pivotal determination. We suggest in particular how supervisors should structure their relationships with semi-public gatekeepers such as lawyers, auditors and consultants to keep abreast of the risk-allocating features of evolving transactional structures. Finally, this paper uses the example of credit funds as non-bank entities economically engaged in credit intermediation to illustrate the merits of the proposed normative framework and to highlight that multipolar regulatory dialogues are needed to shed light on the specific risk-allocating characteristics of recent contractual innovations.
urn:nbn:de:hebis:30:3-616420
Keywords: G21; G28; H77; K22; K23; L22; 330; shadow banking; regulatory arbitrage; principles-based regulation; credit funds; prudential supervision; non-bank financial intermediation